The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.2320/matertrans.m2016375
|View full text |Cite
|
Sign up to set email alerts
|

Deposition of DLC Films onto Oxynitriding-Treated V4E High Vanadium Tool Steel through DC-Pulsed PECVD Process

Abstract: In this work, DLC lms are prepared by DC-pulsed PECVD after the oxynitriding treatment of V4E high vanadium tool steel. The experimental design includes various power densities (200, 400, 600 and 800 mW·cm ) with an unbalanced bipolar-pulsed voltage. The deposition time is 90 min, and the CH 4 gas ow is maintained at 5 sccm, respectively. The experimental results show the duplex coating layers to have better properties when the DLC lms are treated by an appropriate power density (400 mW·cm ) and the highest po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 21 publications
(31 reference statements)
1
8
0
Order By: Relevance
“…A comparison of the corrosion resistance for the different duty cycles of DLC/oxynitriding treated V10 specimens is shown in Table 1. Our previous studies have shown that the samples with a lower current density (I corr ) and high polarization resistance (R P ) evidenced better corrosion resistance [4,5]. In this study, the lowest corrosion current (7.9 × 10 −5 A cm −2 ) and highest polarization resistance (1185.21 Ω cm 2 ) of the V10 specimens appeared at the 17 % duty cycle.…”
Section: Resultssupporting
confidence: 50%
See 4 more Smart Citations
“…A comparison of the corrosion resistance for the different duty cycles of DLC/oxynitriding treated V10 specimens is shown in Table 1. Our previous studies have shown that the samples with a lower current density (I corr ) and high polarization resistance (R P ) evidenced better corrosion resistance [4,5]. In this study, the lowest corrosion current (7.9 × 10 −5 A cm −2 ) and highest polarization resistance (1185.21 Ω cm 2 ) of the V10 specimens appeared at the 17 % duty cycle.…”
Section: Resultssupporting
confidence: 50%
“…As mentioned previously, the oxynitride layer improved not only wear and corrosion resistance but also the intermediate layer. Previous studies indicated that an oxynitride layer could increase DLC films' adhesive strength since passive oxide film (Fe 3 O 4 ) can be used to decrease the microporous structure during the nitriding process [4,5]. In the study, hard and brittle δ-Fe 2 N phases were not found; therefore, the surface brittleness of the oxynitriding layer could be significantly improved.…”
Section: Resultsmentioning
confidence: 82%
See 3 more Smart Citations